Microwave Irradiation of Nanohydroxyapatite from Chicken Eggshells and Duck Eggshells - Nor Adzliana Sajahan; Wan Mohd Azhar Wan Ibrahim (The Scientific World Journal)
Due to similarity in composition to the mineral component of bones and human hard tissues, hydroxyapatite with chemical formula Ca10(PO4)6(OH)2 has been widely used in medical field. Both chicken and duck eggshells are mainly composed of calcium carbonate. An attempt has been made to fabricate nanohydroxyapatite (nHA) by chicken (CES) and duck eggshells (DES) as calcium carbonate source (CaCO3). CES and DES were reacted with diammonium hydrogen [(NH4)2HPO4] solution and subjected to microwave heating at 15 mins. Under the effect of microwave irradiation, nHA was produced directly in the solution and involved in crystallographic transformation. Sample characterization was done using by X-ray diffraction (XRD), fourier transform infrared spectroscopy (FTIR), and scanning electron microscopy (SEM).